Review of microclimate mapping methods in forestry - Sánchez-Chero, Manuel; Sánchez-Chero, José; Flores-Mendoza, Lesly; Navarro, Felix; Donayre, Devyn; Cesare, Mary (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The study of microclimates provides a several benefits that imply their importance to reduce the effects of climate change, so the mapping of microclimates emerges as an alternative for their identification and conservation. The objective of this review is to identify the techniques used in microclimate mapping. The methodology used was an exploratory review in databases such as Science Direct, Springer and IEEXplore, which determined that there is a shortage of works related to microclimate mapping, since only 19 works met the inclusion requirements of the review. It was determined that the main objective of the microclimate mapping focused on the tree canopy, the height and density of the forest structures and their effects on the climatic factors that comprise them. On the other hand, the microclimate mapping methods identified were divided into photogrammetric methods and laser scanning methods, where most of the studies were based on obtaining aerial data, either by drones (UAV, UAS, RPA, RPAS) or airplanes as in the case of airborne LiDAR technologies.  It was concluded that there is little research on microclimate mapping, so the forestry scientific community is exhorted to employ the different methodologies for objectives of great impact on the environment such as the prediction of forest fires and the monitoring of forest restoration after these fires.